Focal dermal hypoplasia: report of a Taiwanese case - Meng-Chi Wu; Sheau-Chiou Chao; Julia Yu-Yun Lee (Wolters Kluwer Medknow Publications, 2011)
Focal dermal hypoplasia (FDH), or Goltz syndrome, is a rare X-linked dominant ectodermal and mesodermal disease involving the skin, distal limbs, and eyes. About 95% of the cases appear de novo, and 90% are females. Recent studies reveal that FDH is caused by mutations in the PORCN gene. Female patients are either heterozygous or mosaic for PORCN mutations, whereas all male patients are mosaic. About 5% of the female patients analyzed have no detectable mutations or microdeletions of PORCN gene. We report a sporadic case of FDH in a 16-year-old girl presenting with atrophic or erythematous macules and patches distributed along the lines of Blaschko over the trunk and extremities with prominent soft yellowish fat herniation over the left axilla and left groin, and papillomas in the oral and genital areas. Multiple developmental anomalies of the digits and ear were also noted. Histopathology of the skin lesion revealed severe dermal hypoplasia. Mutation analysis of all coding regions and flanking intron boundaries of the genomic DNA revealed no detectable mutation of the PORCN gene. Our case manifested mucocutaneous and multiple developmental anomalies typical of FDH, but no mutation in the PORCN gene was detected by mutation analysis.